Etnopedagogic: Nadran as A Source for The Establishment of Social Value of The Cirebon Community - Sarifudin, Arif; Supriatna, Mamat; Peniasiani, Dian (Proceedings International Conference on Education Innovation and Social Science, 2022)
This article is intended to describe the results of a study on Nadran as a source of social value formation in Cirebon society. The approach used in this research is a descriptive qualitative approach with a literature review method, and field studies through observation, interviews, and documentation studies. The data processing technique used is the data triangulation technique. The results of the study indicate that there are social values (gotong royong, and economics) which are the main values in nadran, then there are other supporting values, including: religious values, love for the homeland, and unity. These values can be used as sources in education in elementary schools, so that the quality of students' character is getting better.